Faktor Faktor Yang Berhubungan Dengan Pemeriksaan SADARI Di Wilayah Kerja Puskesmas Bumi Agung Kota Pagar Alam Tahun 2022 - Noviani, Nina; Nuru, Hasanudin; Habibi, FerryJulius (Jurnal Kebidanan Manna, 2023)
This study aims to study the relationship between education and knowledge of mothers about breast cancer with the SADARI examination in the UPTD Puskesmas Bumi Agung area of Pagar Alam City. This study used an analytical survey approach with a cross-sectional design. The population of this study was all WUS in the Bumi Agung Health Centre Working Area of Pagar Alam City. The sample was obtained from as many as 69 people by purposive sampling. Data collection is done using secondary and primary data. Data analysis was performed using the Chi-Square (2) test and the Contingency Coefficient (C) test. The results of the study were obtained: (1) Of the 69 samples there were 28 people who did not do the SADARI examination and 3241 people did the SADARI examination; (2) Of the 69 samples there were 28 people of primary education, 37 people of secondary education and 4 people of higher education; (3) Of the 69 samples there were 14 people of poor knowledge, 16 people of sufficient knowledge and 39 people of good knowledge; (4) There is a significant relationship between education and SADARI examination in the Bumi Agung Health Centre Working Area of Pagar Alam City, with a moderate relationship category and (5) There is a significant relationship between knowledge and SADARI examination in the Bumi Agung Health Centre Working Area of Pagar Alam City, with a moderate relationship category. It is hoped that the health centre can increase public knowledge, especially among women of childbearing age (WUS), by conducting counselling on the importance of conducting SADARI regularly once a month.